The Impact of SQ3R Strategy in Developing the Accuracy of Receiving Volleyball for Students - Shamriu, Ehab Salman Jawad (International Journal of Psychosocial Rehabilitation, 2020)
The goal of the research is to identify the impact of the strategy beyond knowledge according to (SQ3R) in the development of the accuracy of the reception of volleyball transmissions for students, and the researcher assumed that the strategy beyond knowledge according to (SQ3R) positive effect in the development of the accuracy of the reception of volleyball transmissions for students, the researcher touched on Theoretical studies that contained multiple investigations related to the subject of research) strategy beyond knowledge according to (SQ3R), reception of volleyball transmissions, as well as previous studies.The researcher used the experimental method by designing the "two equal groups" with pre and posttests to suit the nature of the research, and identified the research community represented by the fourth-year students in the Faculty of Physical Education and Sports Sciences at the University of Karbala, who numbered 92 students. For the academic year (2018-2019), for the availability of research requirements, the researcher chose the main research sample in a simple random way and in the method of lot, and the size of (28) students, and used appropriate statistical treatments to reach the results, after which the results were presented, analyzed and discussed.